ANALISIS DIKSI, GAYA BAHASA, DAN CITRAAN DALAM EMPAT CERITA ANAK INDONESIA KARYA MURTI BUNANTA - Meliala, Roy Raja Sukmanta; Widodo, Sahid Teguh; Subiyantoro, Slamet (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This research examines four stories of Indonesian children "The Youngest Frog, Si Molek, Masarasenani and The Sun, and also Tiny Boy" by Murti Bunanta. These children's stories come from different region in Indonesia but have similarities and differences in each story. This descriptive analysis uses a stylistic approach that emphasizes the unity of story construction with the theme presented. Elements that are considered and checked are diction, style, and imagery. The result showed is the dominant diction can be seen in denotation with 49 data or 53.85 percentage. The dominant language style can be seen in asidenton language with 16 data or 25.8 percentage. The dominant or multiple images can be seen in visual images with 27 data or 36.99 percentage.